Signal Computing Digital Signals in the Software Domain - Stiber, Michael D.; Zhang Stiber, Bilin; Larson, Eric C.; Open Textbook Library (Open Textbook Library, 2016)
In this book, you will learn how digital signals are captured, represented, processed, communicated, and stored in computers. The specific topics we will cover include: physical properties of the source information (such as sound or images), devices for information cap- ture (microphones, cameras), digitization, compression, digital signal representation (JPEG, MPEG), digital signal processing (DSP), and network communication. By the end of this book, you should understand the problems and solutions facing signal computing systems development in the areas of user interfaces, information retrieval, data structures and algo- rithms, and communications.
1 Signals in the Physical World -- 2 Signals in the Computer -- 3 Filtering and Feedforward Filters -- 4 The Z-Transform and Convolution -- 5 Feedback Filters -- 6 Spectral Analysis -- 7 Compression -- 8 Audio & Video Compression and Coding -- 9 Review and Conclusions
In English.
Description based on online resource
Keywords: Computer Science -- Textbooks